Predictive factors for the effect of pirfenidone in idiopathic pulmonary fibrosis - Ichimura, Yasunori; Tsushima, Kenji; Matsumura, Takuma; Yamagishi, Kazutaka; Abe, Mitsuhiro; Ikari, Jun; Terada, Jiro; Tatsumi, Koichiro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Fibrotic interstitial lung diseases (ILDs) include a number of pulmonary disorders characterized by infiltration of inflammatory cells in lung parenchyma and fibrosis resulting in decreased lung compliance. Idiopathic pulmonary fibrosis (IPF) represents the most common ILD. ILDs can be divided in two anatomo-pathological and radiographic patterns: usual interstitial pneumonitis (UIP) and non-specific interstitial pneumonitis (NSIP). The different radiological features of UIP and NSIP are discussed. The American Thoracic Society, the European Respiratory Society, the Japanese Respiratory Society, and the Latin American Thoracic Association guidelines for the diagnosis and management of IPF have identified several characteristic high-resolution computed tomography (HRCT) features of UIP. However, even if these guidelines recommend to avoid surgical lung biopsy in case of confident UIP diagnosis on HRCT, they present some limitations, the most important of which is represented by interobserver agreement. Magnetic resonance imaging (MRI) can be considered as a radiation-free alternative to HRCT for several lung diseases. However, the clinical value of MRI for IPF diagnosis remains to be proven.